A new species of Buenia (Teleostei: Gobiidae) from the western Mediterranean Sea, with the description of this genus - Kovačić, Marcelo; Ordines, Frances; Schliewen, Ulrich K. (Zootaxa, 2017)
A new miniature gobiid species, Buenia massutii sp. nov. (Teleostei: Gobiidae) is described from the circalittoral bottom off the Balearic Islands, western Mediterranean. Phylogenetic analysis of the mitochondrial COI-barcoding fragment supports its species-level distinctiveness and the monophyly of the genus Buenia. A description and diagnosis of the genus Buenia is for the first time provided. Material of the new species was collected in 57–67 m depth from beam trawl samples carried out on red algae beds. The traits that differentiate the new species from two congeneric species are: anterior oculoscapular canal only semiclosed with pores σ, λ, κ, ω, α, ρ and additional pores and open furrows from interorbital part to pore ρ; posterior oculoscapular canal absent; suborbital row c with 5 papillae; scales in lateral series 26–28; pectoral fin rays 16; the second spine of the first dorsal fin the longest, reaching to or behind posterior end of the second dorsal fin in males when folded down; pelvic fin anterior membrane one sixth or less of length of spinous ray in midline depth; head length 31.2–32.5% of standard length; eye 32.8–35.7% of head length; caudal fin length 21.5–24.0% of standard length.